A Case Manager-Led Pneumonia Care Bundle in a Subacute Rehabilitation Facility. Issue 2 (March 2023) - Granata, Deborah; Kendra, Moira; Chiu, Stephanie H.
Abstract : Purpose of the Study: To evaluate the relationship between a case manager-led pneumonia care bundle at skilled nursing facilities (SNFs) and 30-day hospital readmissions for pneumonia. Primary Practice Settings: The primary practice settings included patients hospitalized with pneumonia at 2 community hospitals between October 2018 and June 2019 and who were subsequently transferred to an SNF. Methodology and Sample: A retrospective cohort study was completed comparing patients in the preintervention cohort who received pneumonia standard of care versus patients in the postintervention cohort who received a case manager-led evidence-based pneumonia care bundle at an SNF. From October 2018 to June 2019, patients admitted with pneumonia to 2 community hospitals in Northwest New Jersey were enrolled in the preintervention cohort. Patients admitted with pneumonia from January 2020 to June 2021 were enrolled in the postintervention group. The primary outcome was to reduce 30-day readmission rates for all patients discharged from the hospital to an SNF with pneumonia. Results: Ninety-nine patients were enrolled in the preintervention cohort and 34 patients were enrolled in the postinterventions cohort. Thirty-day readmission rates were lower in the postintervention cohort (24.2% vs. 17.7%). This reduction in readmission rates was clinically significant, demonstrating a 27% reduction for all patients discharged from the hospital to an SNF with pneumonia. Implications for Case Management Practice: Individualized pneumonia self-management education can be easily implemented in SNFs to improve quality-of-care outcomes for patients. Our health care system collaborates with several SNFs to decrease 30-day hospital readmission. The pneumonia care bundle includes specific measures to improve the transition of care for patients with pneumonia by decreasing the variability of patient care after discharge from the hospital to an SNF. It was hypothesized that to decrease readmissions from the SNFs, we needed to address the quality of care provided by the SNFs by using a 2-prong approach; education of SNF staff on the pneumonia care bundle, and in-person weekly follow-up visits in the SNF until discharge from the SNF to the patient's home.